2020
DOI: 10.3390/metabo10100381
|View full text |Cite
|
Sign up to set email alerts
|

Towards Best Practice in Hair Metabolomic Studies: Systematic Investigation on the Impact of Hair Length and Color

Abstract: Untargeted metabolomic studies are used for large-scale analysis of endogenous compounds. Due to exceptional long detection windows of incorporated substances in hair, analysis of hair samples for retrospective monitoring of metabolome changes has recently been introduced. However, information on the general behavior of metabolites in hair samples is scarce, hampering correct data interpretation so far. The presented study aimed to investigate endogenous metabolites depending on hair color and along the hair s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…An established and optimized procedure described in a previous study was performed to extract metabolites contained in the hair. The previous studies indicated that the use of hair color and segments and its cosmetic treatment were important factors for it as a biospecimen for biomarker discovery by a metabolomics approach. , To avoid the confounding factors from the color and length of hair for comparative study, we selected the black hair and 3 cm segment of hair for biomarker discovery. The hair extracts were analyzed by UHPLC-HRMS with DDA, full scan, and AIF, and the raw data were further processed with MS-DIAL software, which performed peak detection and peak alignment.…”
Section: Methodsmentioning
confidence: 99%
“…An established and optimized procedure described in a previous study was performed to extract metabolites contained in the hair. The previous studies indicated that the use of hair color and segments and its cosmetic treatment were important factors for it as a biospecimen for biomarker discovery by a metabolomics approach. , To avoid the confounding factors from the color and length of hair for comparative study, we selected the black hair and 3 cm segment of hair for biomarker discovery. The hair extracts were analyzed by UHPLC-HRMS with DDA, full scan, and AIF, and the raw data were further processed with MS-DIAL software, which performed peak detection and peak alignment.…”
Section: Methodsmentioning
confidence: 99%
“…Recent progress in hair testing highlights the growing applicability of metabolomics to forensic testing. [116][117][118][119] Heroin and amphetamine-type substances are potentially the most well-known drugs in the wider community and therefore are a focus for forensic toxicology due to their recreational use. Potential heroin biomarkers were investigated in human plasma from 50 participants (20 heroin addicts with acute abstinence, 15 with prolonged abstinence and 15 controls) by Zhou et al using ultraperformance LC-MS/MS.…”
Section: Forensic Toxicologymentioning
confidence: 99%
“…Hair testing is another method suggested for extending the window of detection due to the incorporation of drugs into this matrix. Recent progress in hair testing highlights the growing applicability of metabolomics to forensic testing 116–119 …”
Section: Applicationsmentioning
confidence: 99%
“…The products used for bleaching, perming, dyeing or relaxation contain strong bases, which may affect the stability or the amount of drug present in the hair matrix. These treatments, associated with continuous exposure to natural factors such as sunlight, weather and pollution can contribute to increase the damage in the hair cuticle [64]. In particular, photodegradation of drugs through the formation of free radicals or photosensitization reactions by intermolecular energy transfer can occur when the hair is exposed to sunlight or artificial light for many hours per day [65].…”
Section: Hairmentioning
confidence: 99%